Comorbidity Action in the North: a study of services for people with comorbid mental health and drug and alcohol disorders in the northern suburbs of Adelaide. (December 2016) - Liu, Dennis; de Crespigny, Charlotte; Procter, Nicholas; Kelly, Janet; Francis, Hepsibah; Posselt, Miriam; Cairney, Imelda; Galletly, Cherrie
Objective: This study identified barriers to and facilitators of mental health (MH) and alcohol and drug (AOD) comorbidity services, in order to drive service improvement. Method: Participatory action research enabled strong engagement with community services, including Aboriginal and refugee groups. Surveys, interviews and consultations were undertaken with clinicians and managers of MH, AOD and support services, consumers, families, community advocates and key service providers. Community participation occurred through consultation, advisory and working party meetings, focus groups and workshops. Results: Barriers included inadequate staff training and poor community and workforce knowledge about where to find help. Services for Aboriginal people, refugees, the elderly and youth were inadequate. Service fragmentation ('siloes') occurred through competitive short-term funding and frequent re-structuring. Reliance on the local hospital emergency department was concerning. Consumer trust, an important element in engagement, was often lacking. Conclusions: Comorbidity should be core business of both MH and AOD services by providing consistent 'no wrong door' care. Non-governmental organisations (NGOs) need longer funding cycles to promote stability and retain skilled workers. Comorbidity workforce training for government and NGO staff is required. Culturally appropriate comorbidity services are urgently needed. Despite the barriers, collaboration between clinicians/workers was valued.